A tool for managerial decision making in emerging economies, and asymmetric cost behavior: Evidence from Ecuador - Juan Carlos Aguirre-Quezada; Gabriela Duque-Espinoza; Fernando Córdova-León; Adrián Sigüencia-Muñoz (BBR: Brazilian Business Review)
Business sectors may be affected by changes in their activity levels. For this reason, the administration requires tools that allow to show the impact on its profitability. The asymmetry in the behavior of the costs of companies belonging to the economic sectors of beverage production and meat processing in Ecuador for the period between 2012 and 2018 was analyzed. 291 companies that presented activity were studied. For the study of sticky costs, 3 analysis variables were defined: operational income, total costs and expenses, and personnel costs and expenses; to which, four different study techniques were applied. The different analysis techniques show consistent and robust results, with the exception of the estimation using panel data in the meat sector. The study´s results show an asymmetric behavior within the costs, which suggest an inability for Ecuadorian companies to lower their costs due to a drop on their income, whereas, when their income raises, so does their cost; a fact that matches the recent evidence found worldwide. This asymmetry could be explained by factors such as regulatory rigidity or expectations of a quick business recovery.